(untitled) (Journal of Engineering, 2014)
The increasing use of plastics in various aspects of modern life resulted in the availability of enormous amount of wastes, including a negative effect on the environment and humans. So it is necessary to find solutions to deal with these wastes and ensure to use them as solutions to use in concrete mix . In this research the production of concrete containing high and low density polyethylene has been used by (5, 10, 15)% as a replacement of part of the volume of sand, so as to obtain concrete good compressive strength as well as other benefits such as improved possibility of pumping concrete and reduce the loss of concrete for workability polymer is a material that is non-absorbable of water . It is also intended to dispose of these wastes positively to achieve benefits to the environment and humans alike .